Strengthening Spiritual Leadership in Preserving Religious Culture and Local Wisdom in Madrasah - Siswanto, Siswanto (JURNAL AL-TANZIM, 2022)
This study focused on applying spiritual leadership behavior, religious culture, and local wisdom preserved and its implications on students' character at MTs Sunan Kalijaga Pamekasan Madura. It used a qualitative approach based on phenomenology type. This study found that spiritual leadership behavior in preserving religious culture and local wisdom is reflected by making divine and prophetic values as the foundation of his leadership vision, the spiritual commitment shown in thought, speech, and action, dedicating his efforts as worship. Religious culture leads to individual and social piety through the habituation of reading the Qur'an, praying together, and sympathizing with orphans and poor people. Preserved local wisdom is closely related to Islamic traditions in Madura, such as tatele', Ashura' celebrations, istighatsah, and the Islamic culture of hadrah banjari. This preservation impacts the affective dimension and the growth of student behavior by vertically and horizontally religious values. The spiritual commitment becomes dedication values as a form of worship and empowering personnel by jihad and good service.